2020
DOI: 10.48550/arxiv.2011.04778
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Graph Homomorphism Polynomials: Algorithms and Complexity

Abstract: We study homomorphism polynomials, which are polynomials that enumerate all homomorphisms from a pattern graph H to n-vertex graphs. These polynomials have received a lot of attention recently for their crucial role in several new algorithms for counting and detecting graph patterns, and also for obtaining natural polynomial families which are complete for algebraic complexity classes VBP, VP, and VNP. We discover that, in the monotone setting, the formula complexity, the ABP complexity, and the circuit comple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…The best known algorithms can be expressed as divide-and-conquer algorithms that evaluate small formulas constructed by making use of the graph parameter treedepth. Komarath, Pandey, and Rahul [13] also showed that the running-time of these algorithms match the best possible formula size for all pattern graphs. These arithmetic circuit lower bounds serve as a technical motivation for considering sparse host graphs, in addition to the practical motivation mentioned earlier.…”
Section: Connection To Arithmetic Circuits For Graph Homomorphism Pol...mentioning
confidence: 81%
See 2 more Smart Citations
“…The best known algorithms can be expressed as divide-and-conquer algorithms that evaluate small formulas constructed by making use of the graph parameter treedepth. Komarath, Pandey, and Rahul [13] also showed that the running-time of these algorithms match the best possible formula size for all pattern graphs. These arithmetic circuit lower bounds serve as a technical motivation for considering sparse host graphs, in addition to the practical motivation mentioned earlier.…”
Section: Connection To Arithmetic Circuits For Graph Homomorphism Pol...mentioning
confidence: 81%
“…The graph parameter treedepth plays a crucial role in answering this question. It is well known that we can count the homomorphisms from a pattern of treedepth d in O(n d )-time while using only constant space (See Komarath, Rahul, and Pandey [13] for a construction of arithmetic formulas counting them. These arithmetic formulas can be implicitly constructed and evaluated in constant space.).…”
Section: :2mentioning
confidence: 99%
See 1 more Smart Citation
“…As formulas can be thought of as bounded space analogies of circuits, Theorem 4 gives further evidence (in addition to e.g. [9,24,31]) supporting that while treewidth is the right parameter for CSP-like problems when equipped with unlimited space, treedepth is the right parameter when dealing with bounded space.…”
Section: Mwis-formulas and Treedepthmentioning
confidence: 82%
“…Multiple worst-case lower bounds of form n Ω(w) in limited models of computation for graph homomorphism problems of a pattern graph with treewidth w to a graph with n vertices are known [4,24,25]. In particular, recently it was shown that the worst-case monotone arithmetic circuit complexity of homomorphism polynomial is Θ(n w+1 ), and the worst-case arithmetic formula complexity is Θ(n t ), where t is the treedepth of the pattern graph [24].…”
Section: Related Workmentioning
confidence: 99%